Prevalence of homozygosity for the deleted alleles of glutathione S-transferase mu (GSTM1) and theta (GSTT1) among distinct ethnic groups from Brazil: relevance to environmental carcinogenesis? - Arruda, Valder Roberval (1998)
Marilda de Souza Gonçalves “Documento produzido em parceria ou por autor vinculado à Fiocruz, mas não consta à informação no documento”.